2012
DOI: 10.1111/j.1750-3841.2011.02583.x
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Sediment Formation in Green Tea Infusions

Abstract: The formation of irreversible tea sediment (IRS) and its chemical components in green tea infusions were investigated. The results showed that the amounts of IRS in the green tea infusions from various tea cultivars ranged from 0.10 to 1.47 mg/mL. The amount of IRS was influenced remarkably by the chemical components in the green tea infusion. Principal component analysis and regression analysis indicated that gallated catechins, Mn, Ca, caffeine, Na, and (-)-gallocatechin gallate (GCG) were the principal comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
1
8
0
1
Order By: Relevance
“…A positive value of ΔG portrays that the catechin will not be able to replace gallic acid from the CG co‐crystal. The experiments reveal that catechin neither precipitates out of the solution nor allows the caffeine‐gallic acid co‐crystal to precipitate, because catechin increases the solubility of caffeine and does not allow its precipitation at 300 K. Xu et al () and Chao and Chiang () had shown that the gallated catechins are mostly responsible for tea cream formation as their structures offer more hydroxyl groups for hydrogen bonding, which was thought to be an important force for aggregation of compounds involved in tea cream formation. However, without gallate structure, catechin seem to increase solubility of caffeine in solutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive value of ΔG portrays that the catechin will not be able to replace gallic acid from the CG co‐crystal. The experiments reveal that catechin neither precipitates out of the solution nor allows the caffeine‐gallic acid co‐crystal to precipitate, because catechin increases the solubility of caffeine and does not allow its precipitation at 300 K. Xu et al () and Chao and Chiang () had shown that the gallated catechins are mostly responsible for tea cream formation as their structures offer more hydroxyl groups for hydrogen bonding, which was thought to be an important force for aggregation of compounds involved in tea cream formation. However, without gallate structure, catechin seem to increase solubility of caffeine in solutions.…”
Section: Resultsmentioning
confidence: 99%
“…The green tea is prepared with unfermented tea leaves, whereas oolong tea and black tea are prepared using semi‐fermented and fermented tea leaves, respectively. When hot aqueous tea infusion is cooled, solid sediment called “tea cream” precipitates consisting mainly of caffeine, polyphenols, organic acids, and theaflavins (Chao & Chiang, ; Jöbstl, Fairclough, Davies, & Williamson, ; Wickremasinghe & Perera, ; Xu et al, ; Xu, Chen, Yuan, Tang, & Yin, ; Yin, Xu, Yuan, Luo, & Qian, ). The formation of the tea cream depends on temperature, concentration, and chemical composition (Bee, Izzard, Harbron, & Stubbs, ; Jöbstl et al, ; Liang & Xu, ; Xu et al, ; Xu et al, ; Yin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Tea sediment consists of reversible tea sediment (RTS) primarily and irreversible tea sediment (IRS) (Xu et al, 2014). The main chemical composition of RTS is very different from that of IRS, especially the mineral composition (Xu, Chen, Wang, et al, 2012). RTS mainly comprises polyphenols, total sugar, caffeine, flavones and proteins, and IRS consists of oxalates of Ca, Mg, Ga and Mn (Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrates are the most abundant chemical components in ginseng, followed by protein [9]. Part of the sediment can be reheated and reconstituted into reversible sediment (RS), and the irreversible part is called irreversible sediment (IRS), which is similar to the sediment in green tea [10]. The common phenomenon of turbidity in beverages is a result of polyphenol-protein interactions, which bind noncovalently and are reversible in the early stage of sediment formation [11].…”
Section: Introductionmentioning
confidence: 99%